Chuj (Mayan) Narratives : Folklore, History, and Ethnography from Northwestern Guatemala - Hopkins, Nicholas A. (Book collections on Project MUSE., 2021)
"Analyzes six narratives that illustrate the breadth of the (relatively isolated) Mayan Chuj storytelling tradition, from ancient mythology to current events and from intimate tales of local affairs to borrowedstories"--